By-Laws, Rules and Regulations : 2006. (By Laws, Rules and Regulations; Sixtieth Issue, May, 2006, 2006)
The By-Laws are adopted under the authority of, and are intended to be complementary to, the Articles of Agreement of the International Monetary Fund; and they shall be construed accordingly. These Rules and Regulations supplement the Articles of Agreement and the By-Laws adopted by the Board of Governors. They are not intended to replace any provision of either the Articles or the By-Laws. The Rules and Regulations provide such operating rules, procedures, regulations, and interpretation as are necessary and desirable to carry out the purposes and powers contained in the Articles, as supplemented by the By-Laws. If any provision in the Rules and Regulations is found to conflict with any provision in the Articles or in the By-Laws, the Articles and By-Laws shall prevail, and an appropriate amendment shall be made to these Rules and Regulations. Additions to, and changes of, the Rules and Regulations will be made as experience brings to light new problems or suggests modifications in procedures already adopted.